2013
DOI: 10.3389/fnbeh.2013.00060
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Symptomatic Aspects of Rapid Eye Movement Sleep in a Mouse Model of Posttraumatic Stress Disorder

Abstract: Not every individual develops Posttraumatic Stress Disorder (PTSD) after the exposure to a potentially traumatic event. Therefore, the identification of pre-existing risk factors and early diagnostic biomarkers is of high medical relevance. However, no objective biomarker has yet progressed into clinical practice. Sleep disturbances represent commonly reported complaints in PTSD patients. In particular, changes in rapid eye movement sleep (REMS) properties are frequently observed in PTSD patients. Here, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 120 publications
(207 reference statements)
3
14
0
Order By: Relevance
“…In addition, many known interactions between distinct aspects of stress and sleep biology were observed. This includes well-known physiological relationships, such as body weight measurements and plasma glucose levels (Figure 2C and G), as well as previously reported associations between sleep and stress traits, such as conditioned fear and REM sleep (Figure 2B and F) (Menz et al, 2013; Polta et al, 2013). Other phenotypic relationships were also observed.…”
Section: Resultssupporting
confidence: 77%
“…In addition, many known interactions between distinct aspects of stress and sleep biology were observed. This includes well-known physiological relationships, such as body weight measurements and plasma glucose levels (Figure 2C and G), as well as previously reported associations between sleep and stress traits, such as conditioned fear and REM sleep (Figure 2B and F) (Menz et al, 2013; Polta et al, 2013). Other phenotypic relationships were also observed.…”
Section: Resultssupporting
confidence: 77%
“…The general sleep/wake behavior of our young control animals (Figures 1, 2) is in accordance with previous findings in the literature on WAKE, NREMS, and REMS distribution in C57BL/6J mice (Tobler et al, 1997) and in C57BL/6N mice (Polta et al, 2013). Our old control mice expressed increased amounts of NREMS at the beginning of the active period, when compared to the young animals of the same group.…”
Section: Discussionsupporting
confidence: 92%
“…All recording electrodes, consisting of gold wire (diameter: 150 μm, Häfner, München, Germany) with ball-shaped endings were soldered to a PCP socket board (Type 861-87-008-10-001101, preci-dip, Switzerland), which was later connected to the pre-amplifier and the recording cable. For a detailed description of the surgical procedure and electrode design, please refer to Fulda et al (2011) and Polta et al (2013). During and after surgery, animals received analgesic treatment (Meloxicam, 0.5 mg/ml suspension, s.c. injection and 5 × 10 −4 mg/ml for 7 days in drinking water).…”
Section: Methodsmentioning
confidence: 99%
“…There is some early evidence that individual differences in immune response (74) predict trauma response in the SDS model. Furthermore, another study demonstrated that low hippocampal levels of N-acetylaspartate assessed by proton magnetic resonance spectroscopy and differences in pre-trauma REM predicted persistent susceptibility to inescapable shocks in mice (17; 88).…”
Section: Discussionmentioning
confidence: 99%
“…Susceptible and resilient animals have been defined by success or failure to escape subsequent shock exposures (16). Interestingly, REM immediately before (24 hrs) foot-shock exposure predicts long-term emergence of hyperarousal after the foot-shock protocol (17), suggesting that this paradigm may be useful in examining treatments. This paradigm also induces enhanced neuronal activity in the PFC and amygdala and decreased volume in the hippocampus (13; 18–23) (Table 2).…”
Section: Introductionmentioning
confidence: 99%